Survival of non-symbiotic nitrogen-fixing bacteria in the rhizosphere of sorghum (Sorghum vulgare Pers.) - Carneiro, Adilson Martins; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse experiment was conducted to study the influence of sorghum (Sorghum vulgare) plants, liming and nitrogenous fertilization on Azotobacter and Beijerinckia population in an acid soil. This experiment included combinations of the basic treatments: pots with and without plants, with and without lime and with and without nitrogenous fertilizer. All the pots received the same fertilization with phosphorus, potassium and minor elements, as well as inoculations with several species of Azotobacter and Beijerinckia. The study of the influence of these treatments was made by counting the microcolonies of bacteria growing on silical-gel plates in consecutive periods. Liming stimulated Azotobacter growth which almost disappeared in the unlimed pots (pH 5.0). The sorghum did not affect the development of Azotobacter, except in the pots with lime and with N. Nitrogenous fertilizing was harmful to Azotobacter and Beijerinckia alike. Liming stimulated Beijerinckia growth but less than that of Azotobacter. Sorghum strongly stimulated Beijerinckia growth, a confirmation of experiments made with other grasses. Nitrogenous fertilization caused a fall in the pH of the soil in the pots treated with lime.